Globalization and Migrant Rights in Post-Pandemic Italy: Navigating Economic Dependency and Policy Exclusion - Nicolosi, Davide; Licaj, Lindita; Lakshman, Iresha M. (European Scientific Journal, ESJ, 2025)
The study examines the impact of globalization on migration governance and migrant rights in post-pandemic Italy, emphasizing the contrasts between the country’s economic reliance on migrant labour and the enforced, more restrictive policies. The research employs a qualitative, desk-based approach to analyse how migration flows have changed due to globalization, the primary human rights problems faced by immigrants, the effects of Italian and EU migration policies, and the socio-economic barriers to integration. The study examines the impact of border securitization, labour market conditions and the COVID-19 pandemic on migrant experiences, with a focus on the increasing importance of civil society and grassroots activism in advocating for migrant rights. By analysing academic literature, policy documents and institutional reports, this research aims to provide a critical understanding of the challenges facing migrants in Italy and how current policies influence their access to legal protections, employment and long-term social stability.